A Delphi study on teacher trainees’ competencies to promote cultural sustainability of Chinese traditional musical instrument education / Zhang Jiaxin ... [et al.] - Zhang, Jiaxin; Muthukrishnan, Priyadarshini; Teoh, Sian Hoon; Gao, Xiaobao; Liu, Chengxuan (Universiti Teknologi MARA, 2024)
This study aimed to use the Delphi method to identify the core competencies required of teacher trainees to effectively promote the educational and cultural sustainability of traditional Chinese musical instruments. This study systematically collected and condensed the views of five experts on this topic through three rounds of expert surveys and eventually reached a consensus. Currently, traditional Chinese musical instrument education faces a lack of professional teachers, a lack of systematic teaching methods, and a lack of enthusiasm among teachers and students, making effective teacher training crucial. However, previous research on the education and training of traditional Chinese musical instruments for trainees is insufficient and there are no clear guidelines on the competencies needed for trainee teachers to meet future educational needs. This study identified 18 core competencies and classified the competencies needed by teacher trainees in traditional Chinese musical instrument education into three dimensions: musical knowledge, teaching skills, and cultural attitude based on a competency-based model. The results of this study will provide clear guidelines for teacher training programs to improve the quality of education and ensure the preservation and promotion of traditional Chinese music culture in contemporary society, thus contributing to the achievement of SDG 4: Quality Education.